Comparative Evaluation of Bone Repair with Four Different Bone Substitutes in Critical Size Defects - Grossi-Oliveira, Gustavo [UNESP]; Faverani, Leonardo P. [UNESP]; Mendes, Bruno Coelho [UNESP]; Braga Polo, Tárik Ocon [UNESP]; Batista Mendes, Gabriel Cury; Lima, Valthierre Nunes De [UNESP]; Ribeiro Júnior, Paulo Domingos; Okamoto, Roberta [UNESP]; Magro-Filho, Osvaldo [UNESP] (Hindawi, 2020)
This study evaluated the osteoconductive potential of four biomaterials used to fill bone defects. For this, 24 male Albino rabbits were submitted to the creation of a bilateral 8 mm calvarial bone defect. The animals were divided into four groups - bovine hydroxyapatite, Bio-Oss® (BIO); Lumina-Bone Porous® (LBP); Bonefill® (BFL); and an alloplastic material, Clonos® (CLN) - and were euthanized at 14 and 40 days. The samples were subjected to histological and histometric analysis for newly formed bone area. Immunohistochemical analysis for Runt-related transcription factor 2 (Runx2), vascular endothelial growth factor (VEGF), and osteocalcin (OC) was performed. After statistical analysis, the CLN group showed greater new bone formation (NB) in both periods analyzed (p<0.05). At 14 days, the NB showed greater values in BIO in relation to LBP and BFL groups; however, after 40 days, the LBP group surpassed the results of BIO (p<0.001). The immunostaining showed a decrease in Runx2 intensity in BIO after 40 days, while it increased for LBP (p<0.05). The CLN showed increased OC compared to the other groups in both periods analyzed (p<0.05). Therefore, CLN showed the best osteoconductive behavior in critical defects in rabbit calvaria, and BFL showed the lowest osteoconductive property.